QUALITY MANAGEMENT - A NEW CONCEPT OF CONTROL IN MACHINE-BUILDING ENTERPRISES - Аксьонова, Людмила Іванівна (Eastern-European Journal of Enterprise Technologies, 2010)
The paper analyzes the status and trends of the introduction of modern quality management systems (QMS) at the Ukrainian machine-building enterprises. The reasons that hinder the development and improvement of QMS business were considered. The role of internal audit of QMS to improve the engineering enterprise was shown.